‘Rolling’ stoneflies (Insecta: Plecoptera) from mid-Cretaceous Burmese amber - Pavel Sroka (PeerJ, 2018)
This contribution describes seven new species of fossil stoneflies from Cretaceous Burmese amber, all of which are dedicated to present and past members of the Rolling Stones. Two species—Petroperla mickjaggeri gen. nov. sp. nov. and Lapisperla keithrichardsi gen. nov. sp. nov.—are placed in a new family Petroperlidae within the stemline of Systellognatha. The first Cretaceous larval specimen of Acroneuriinae, Electroneuria ronwoodi gen. nov. sp. nov., is also described along with another four new species that are placed within the Acroneuriinae genus Largusoperla Chen et al., 2018: Largusoperla charliewattsi sp. nov., Largusoperla brianjonesi sp. nov., Largusoperla micktaylori sp. nov., and Largusoperla billwymani sp. nov. Additional specimens of Acroneuriinae are described without formal assignment to new species due to insufficient preservation. Implications for stonefly phylogeny and palaeobiogeography are discussed.